African Traditional Semiotics: The Example of ‘AR’OKO’ in Yoruba Tradition - Abdullahi-Idiagbon, M.S. (Signs - International Journal of Semiotics, 2009)
Researches in humanities, social sciences have all established the social nature of man which simply means man’s ability to interact with one another through various communicative means. This paper, while advancing a semiotic maxim that “everything is a sign”, cautions that since meaning is the creation of man, the (meaning) signification of a sign may vary from time to time and culture to culture. It thus examines the concept, content, form and context of “Aroko” within the Yoruba cultural setting as an effective semiotic code used either as an alternative or as a complementary communicative means.